Revisiting lead isotope data in Shang and Western Zhou bronzes. (6th December 2017) - Jin, Zhengyao; Liu, Ruiliang; Rawson, Jessica; Pollard, A. Mark
Abstract: Abstract : Lead is a major component of Chinese ritual bronze vessels. Defining its sources and usage is thus highly significant to understanding the metal industries of the Chinese Bronze Age. A new, simplified method has been developed for examining data, thereby providing insight into diachronic change in the origins of lead sources used in artefacts. Application of this method to the existing corpus of lead isotope data from the Erlitou ( c. 1600 BC) to the Western Zhou ( c. 1045–771 BC) periods reveals changes in the isotope signal over this time frame. These changes clearly reflect shifts in the sourcing of ores and their use in metropolitan foundries. Further data are required to understand these complex developments.